2021
DOI: 10.1002/ange.202113443
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Synthesis of Poly(silylether)s: Access to Degradable Polymers from Renewable Resources

Abstract: The design of new materials with tunable properties and intrinsic recyclability, derived from biomass under mild conditions, stands as a gold standard in polymer chemistry. Reported herein are platinum complexes which catalyze the formation of poly(silylether)s (PSEs) at low catalyst loadings. These polymers are directly obtained from dual-functional biobased building blocks such as 5-hydroxymethylfurfural (HMF) or vanillin, coupled with various dihydrosilanes. Access to different types of copolymer architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…PR11 micelle has a silyl ether linkage (–Si–O–C–), which can be cleavaged under acidic and even upon basic conditions. 91,92 This silyl ether bond was hydrolyzed at pH 1.2 to obtain silanols and alcohols as byproducts, releasing curcumin from the micelle core. The breaking of the –Si–O–C– bond has also been reported under basic conditions, obtaining byproducts similar to those at acidic pH; however, the degradation of the micelle is slower.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PR11 micelle has a silyl ether linkage (–Si–O–C–), which can be cleavaged under acidic and even upon basic conditions. 91,92 This silyl ether bond was hydrolyzed at pH 1.2 to obtain silanols and alcohols as byproducts, releasing curcumin from the micelle core. The breaking of the –Si–O–C– bond has also been reported under basic conditions, obtaining byproducts similar to those at acidic pH; however, the degradation of the micelle is slower.…”
Section: Resultsmentioning
confidence: 99%
“…The breaking of the –Si–O–C– bond has also been reported under basic conditions, obtaining byproducts similar to those at acidic pH; however, the degradation of the micelle is slower. 91,92 In addition, these byproducts are not toxic to cells, 93 so PR11 micelles could be an alternative to hydrophobic drug delivery, especially for curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the degradability and potential chemical recyclability of our polycarbonates were investigated. Methanolysis is one of the most commonly used protocols to study the degradation behavior of polymers, 64,65 although ethanol has already been shown to be more effective than methanol in degrading certain polymers such as PC. 66,67 In addition, it has been widely reported that polycarbonates are resistant to methanolysis in the absence of catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…They are widely used as oils, rubbers, silicone resins, heat-resistant materials and optoelectronic materials, because of their excellent thermal, electronic and optical properties. 23–26 Progress has been made towards the application of organocatalytic step-growth polymerizations in the synthesis of organosilicon polymers, with such reactions including dehydrogenative coupling, 27–32 hydrosilylation of silanes with ketones, alkenes or alkynes, 33–37 the Piers–Rubinsztajn reaction 38,39 and others. 40,41 Using the indole skeleton to construct polymeric materials has also attracted intense attention.…”
Section: Introductionmentioning
confidence: 99%